Determinants of Total Factor Productivity of Libyan banks 2004 – 2010 - Alrafadi, Khalad M. S. (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
The paper examines the determinants of Total Factor Productivity (TFP) of Libyan banks by employing Data Envelopment Analysis (DEA) based Malmquist Productivity Index (MPI) and Ordinary Least Square (OLS) estimation regression model for the period 2004 – 2010. For estimate TFP and determinants in this study we used DEAP 2.1 software and we used Evies 7 software for estimating determinants. The results showed that our variables which used in this study are not significant related to TFP.